Method for determining coordinates of airborne objects by radars with additional use of ADS-B receivers - Khudov, Hennadii; Diakonov, Oleksii; Kuchuk, Nina; Maliuha, Volodymyr; Furmanov, Kostiantyn; Mylashenko, Ihor; Olshevskyi, Yurii; Stetsiv, Stanislav; Solomonenko, Yuriy; Yuzova, Iryna (Eastern-European Journal of Enterprise Technologies, 2021)
The method of determining coordinates of an airborne object using ADS-B receivers was improved. The method involves the following sequence of actions: input of initial data, measurement of coordinates of the airborne object by the radar, checking the availability of data about the airborne object obtained from the ADS-B receivers. In the absence of such data, coordinates of the airborne object are determined only from the data of the radar. The airborne object mark was identified according to information from the radar and the ADS-B receivers. Unlike the known methods, the advanced method of determining coordinates of an airborne object by a radar additionally uses information from the ADS-B receivers. The ADS-B receiver signals were experimentally studied. It was found that the ADS-B receiver has received more than 6,000 messages about airborne objects in a single day. It was established that information about the location of the airborne object contained in ADS-B messages was encoded in CPR format. An algorithm for decrypting the ADS-B messages with a global connection of an airborne object to geographical coordinates was presented. An algorithm for detecting signals of onboard transponders of ADS-B airborne objects was presented. Non-standard ADS-B messages from airborne objects were studied. It was suggested that some short non-standard ADS-B messages were received from small and military airborne objects. Accuracy of determining coordinates of airborne objects by the radar with additional use of the ADS-B receiver was estimated. Dependence of the root mean square error of determining the airborne object coordinates on a distance to the airborne object was presented for various cases. It was established that the accuracy of determining the airborne object coordinates can be raised from 36 % to 67 % depending on the distance to the airborne object